Clinical efficacy of dual-phase scanning using 68Ga-DOTATOC-PET/CT in the detection of neuroendocrine tumours. Issue 10 (October 2016) - Nakamoto, Y.; Ishimori, T.; Sano, K.; Temma, T.; Ueda, M.; Saji, H.; Togashi, K.
Abstract : Aim: To investigate whether delayed scanning at approximately 90 minutes post-injection of 68 Ga-labelled 1, 4, 7, 10-tetraazacyclododecane- N, N ′, N ″, N ‴-tetraacetic acid-d -Phe 1 -Tyr 3 -octreotide (DOTATOC) had any clinical benefits regarding the evaluation of neuroendocrine tumours (NETs), relative to conventional combined positron-emission tomography (PET) and computed tomography (CT) at 60 minutes post-injection. Materials and methods: Fifty-four patients who underwent DOTATOC-PET/CT for suspected or known NETs were retrospectively reviewed. PET/CT was performed twice at approximately 60 and 90 minutes post-injection. For visual analysis, a five-point grading scale (0: definitely normal to 4: definitely abnormal) was used, and grade 3–4 lesions were regarded as positive. For quantitative analysis, the time course of the maximum standardised uptake value (SUVmax) in each lesion and the mean SUV of physiological uptake in the liver were evaluated. Results: Of the 54 patients, 43 had a total of 132 lesions. In interpreting the early images, there were four grade 3 lesions, and the remaining 128 lesions were grade 4. All 132 lesions were grade 4 in the delayed images. SUVs and tumour-to-liver ratios for hepatic lesions were slightly higher in delayed scanning than in early scanning (SUV, 26.8±21.2 versus 28.2±21.2 [ p <0.01]; tumour-to-liver ratio, 5.9±4.5 versus 6.2±4.6 [ p <0.01]), which did not affect the detection rate. Additionally, bone and peritoneal metastases had slightly higher SUVs at delayed imaging ( p <0.05), but there was no difference in diagnostic performance. No significant difference in the SUVs for pancreatic lesions and primary sites in the bowel were observed between the early and delayed scans. Conclusion: Delayed scanning may be helpful for improving diagnostic confidence in some cases, although it provided no specific merits for diagnostic accuracy in detecting primary or metastatic NETs. Highlights: Quantitative values were larger in delayed scan in some organs or lesions. The delayed scan provided no specific merits for diagnostic accuracy. Dual phase DOTATOC-PET/CT may be helpful in improving confidence in some cases.